Variability in hemoglobin mass response to altitude training camps. (9th September 2020) - Nummela, Ari; Eronen, Timo; Koponen, Anne; Tikkanen, Heikki; Peltonen, Juha E.
Abstract : The present study investigated whether athletes can be classified as responders or non‐responders based on their individual change in total hemoglobin mass (tHb‐mass) following altitude training while also identifying the potential factors that may affect responsiveness to altitude exposure. Measurements were completed with 59 elite endurance athletes who participated in national team altitude training camps. Fifteen athletes participated in the altitude training camp at least twice. Total Hb‐mass using a CO rebreathing method and other blood markers were measured before and after a total of 82 altitude training camps (1350‐2500 m) in 59 athletes. In 46 (56%) altitude training camps, tHb‐mass increased. The amount of positive responses increased to 65% when only camps above 2000 m were considered. From the fifteen athletes who participated in altitude training camps at least twice, 27% always had positive tHb‐mass responses, 13% only negative responses, and 60% both positive and negative responses. Logistic regression analysis showed that altitude was the most significant factor explaining positive tHb‐mass response. Furthermore, male athletes had greater tHb‐mass response than female athletes. In endurance athletes, tHb‐mass is likely to increase after altitude training given that hypoxic stimulus is appropriate. However, great inter‐ and intra‐individual variability in tHb‐mass response does not support classification of an athlete permanently as a responder or non‐responder. This variability warrants efforts to control numerous factors affecting an athlete's response to each altitude training camp.